Beyond the Binary: Investigating the Differential Effects of Microcredit on Poor and Near-Poor Households - NGUYEN, Quynh Hoa,; VU, Cuong,; NGO, Quoc Dung,; HOANG, Vu Hiep, (Journal of Ecohumanism, 2024)
This study employs difference-in-differences methodology to examine the impact of formal microcredit on income levels of poor and near-poor households in Vietnam using panel data from 2016-2018. Findings reveal microcredit participation leads to a 0.021% increase in average income over time, with loan size, purpose, and household characteristics significantly influencing outcomes. The research contributes a nuanced analysis of microcredit’s differential effects across income groups, incorporating credit use as a key variable. Results have implications for designing targeted interventions maximizing microcredit’s poverty alleviation potential. Policymakers should promote productive credit use and support services tailored to borrowers’ needs.